The Jotas in Laguna a dance movement study - Buot, Merites M. (College of Human Kinetics, University of the Philippines Diliman, 2003)
The study was conducted to document in video and compare the similarities and differences in the dance movements of three (3) jotas in Laguna, Philippines namely: Jota Italiana, Jota Sevillana and A la Jota. The study used a complementation of document analysis, key informant interview (KII) and field observation in gathering and interpreting data. Published dance notations of the particular dances were gathered and used for the analysis.Results showed that there were similarities and differences of the three jotas in Laguna. With respect to foot movement there were three common steps (25% similar) out of the twelve total number of steps found in three jotas. These were the waltz step, stamp and the turn. A La Jota and Jota Italiana were similar in six out of the twelve total number of steps (50% similar) of foot movement. Jota Sevillana, although 25% similar with the other two jotas, had five distinctly unique foot movement out of twelve total number of steps (42% unique) as compared with A La Jota of San Pablo City and Jota Italiana of Paete, Laguna. On the other hand, Jota Italiana had one exclusive foot movement, the leap that was not present in the other jotas, while A La Jota had no unique movement. With respect to the torso/trunk movement, the three jotas had three similar movements out its four total number of movements (75% similar). In Jota Italiana and A La Jota, all the torso/trunk movements were similar. Jota Sevillana had one different movement (25%) from the other two jotas, which is the pulling of partners towards each other. There were three out of the eight (38%) total number of arm/hand movements that were similar in the three jotas; the lateral arm, holding of hands and the reverse T arm position, while A La Jota and Jota Italiana have all similar arm/hand movements. The similarity in movements could mean that the different jotas were once coming from one source while the differences could be attributed to the localized differences in culture and stylistic interpretation. Periodic documentation of dances in general should be done. Analytical researches considering different aspects of culture and society should be undertaken. Finally, the revival of the jota dances in schools and festivals should be encouraged.